PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS VIDEO ANIMASI PADA MATERI MASA PRA-AKSARA DI INDONESIA PESERTA DIDIK KELAS X.1 SMA NEGERI 1 BANDAR LAMPUNG - Sri Ani, Ketut; Wisnu Kurniawan, Putut; Nandia F, Aurora (Universitas Batanghari Jambi, 2025)
This research is motivated by the lack of use of learning media, low interest in learning students, and learning media that are often used are still in the form of power points and printed books. This study aims to determine the development, eligibility and response of students to animated video learning media in learning the history of Pre-Ancient Period material class X.1 SMA Negeri 1 Bandar Lampung. The research method used is R&D (research and development) and through the ADDIE development procedure, and through the ADDIE development procedure which consists of analysis, design, development, implementation, and evaluation. Product validation was completed by linguist validators who stated that the animated video learning media for learning the history of the Pre-Ancient Period material developed obtained an assessment result of 4.6 with the interpretation criteria “very valid”, while the results of the material expert validation stated that the animated video learning media for learning the history of the Pre-Ancient Period material developed obtained an assessment result of 4.5 with the interpretation criteria “very valid”, then the results of the media expert validation stated that the animated video learning media for learning the history of the Pre-Ancient Period material developed obtained an assessment result of 4.2 with the interpretation criteria “very valid”. While the response of students in the field trial obtained an average score of 4.4 with the interpretation criteria of “very practical”. The development of animated video learning media for learning the history of Pre-Ancient Period material for class X.1 SMA Negeri 1 Bandar Lampung students using the research and9development (R&D) research method, it can be concluded that the use of animated video learning media for learning the history of Pre-Ancient Period material is very valid and very practical to use as learning media.